Informed consent, participation in, and withdrawal from a population based cohort study involving genetic analysis. Issue 7 (30th June 2005) - Matsui, K; Kita, Y; Ueshima, H
Abstract : Objective: Population based cohort studies involving genetic research have been initiated in several countries. However, research published to date provides little information on the willingness of the general population to participate in such studies. Furthermore, there is a need to discover the optimal methods for acquiring fully informed consent from the general population. We therefore examined the results of a population based genetic cohort study to identify the factors affecting the participation rate by members of the general public and also specifically to examine the impact of different consent procedures on the rate of participation by prospective candidates and their subsequent withdrawal rate from the study. Design: Descriptive analyses. Setting and participants: The study evaluated two non-genetic subcohorts comprising 3166 people attending for a health checkup during 2002, and two genetic subcohorts comprising 2195 people who underwent a checkup during 2003. Main outcome measurements: Analysis endpoints were differences in participation rates between the non-genetic and genetic subcohorts, differences between providing non-extensive and extensive preliminary information, and changes in participation status between baseline and at 6 months. Results: Participation rates in the genetic subcohorts were 4·7–9·3% lower than those in the non-genetic subcohorts. The odds ratios (OR) of participation in genetic research were between 0·60 and 0·77, and the OR for withdrawal from the research was over 7·70; providing preliminary extensive information about genetic research reduced the withdrawal risks (OR 0·15 for all dependent variables) but worsened participation rates (OR 0·63–0·74). Conclusions: The general population responded sceptically towards genetic research. It is crucial that genetic researchers utilise an informative and educational consent process worthy of public trust.